Retargeted oncolytic adenovirus displaying a single variable domain of camelid heavy-chain-only antibody in a fiber protein - van Erp, Elisabeth A (Mol Ther Oncolytics, 2015)
Conditionally replicative adenoviruses are promising agents for oncolytic virotherapy. Various approaches have been attempted to retarget adenoviruses to tumor-specific antigens to circumvent deficiency of receptor for adenoviral binding and to provide an additional level of tumor specificity. Functional incorporation of highly specific targeting molecules into the viral capsid can potentially retarget adenoviral infection. However, conventional antibodies are not compatible with the cytoplasmic adenovirus capsid synthesis. The goal of this study was to evaluate the utility of single variable domains derived from heavy chain camelid antibodies for retargeting of adenovirus infection. We have combined transcriptional targeting using a tumor-specific promoter with transductional targeting through viral capsid incorporation of antihuman carcinoembryonic antigen single variable domains. Obtained data demonstrated that employment of a single variable domain genetically incorporated into an adenovirus fiber increased specificity of infection and efficacy of replication of single variable domain-targeted oncolytic adenovirus. The double targeting, both transcriptional through the C-X-C chemokine receptor type 4 promoter and transductional using the single variable domain, is a promising means to improve the therapeutic index for these advanced generation conditionally replicative adenoviruses. A successful strategy to transductional retargeting of oncolytic adenovirus infection has not been shown before and therefore we believe this is the first employment of transductional targeting using single variable domains derived from heavy chain camelid antibodies to enhance specificity of conditionally replicative adenoviruses.